The Effect of a Mindfulness Prescription on Emotional Eating and Happiness in Obese Individuals - Aysel Akbeniz; Fatma Melike Akar; Abdurrezzak Gültekin; Funda Kavak Budak (Bariatric Surgical Practice and Patient Care, 2026)
Background: This study aimed to determine the effect of a mindfulness prescription on emotional eating and happiness in obese individuals. Methods: This randomized controlled study included 132 obese individuals (control group n = 66; intervention group: n = 66). The intervention group received a 12-session mindfulness prescription, while the control group received no intervention. Data were collected using a Descriptive Characteristics Form, the Emotional Eating Scale, and the Happiness Scale. Results: No statistically significant difference was found between the pretest and posttest total mean scores of the Emotional Eating and Happiness Scales in the control group ( p > 0.05). In contrast, the intervention group showed a statistically significant difference between pretest and posttest scores on both scales ( p < 0.05). Conclusion: The intervention group demonstrated decreased emotional eating and increased happiness levels compared with the control group at posttest, indicating short-term effectiveness of the mindfulness prescription. As follow-up data were not collected, long-term effects could not be assessed.